Predictors of the presence of typical atrial flutter in patients undergoing atrial fibrillation ablation. (3rd October 2022) - Ulus, T; Yilmaz, A S; Al, A; Sener, E; Durmaz, F E
Abstract: Background: Typical cavotricuspid isthmus (CTI) dependent atrial flutter (Afl) may develop spontaneously in patients undergoing atrial fibrillation (AF) ablation and it is also responsible for a significant portion of recurrences after AF ablation. In this situation, the second ablation for typical Afl is frequently needed. If the predictors of typical Afl can be known in such patients, CTI ablation for typical Afl can also be performed in the same session as AF ablation. Thus, the risks and increased costs of the second ablation procedure can be avoided. There is insufficient data related to the predictors of typical Afl in patients undergoing AF ablation. Purpose: In this study, we aimed to investigate the predictors of typical Afl in patients undergoing catheter ablation for AF. Methods: In this retrospective study, we consecutively enrolled 135 patients with AF undergoing index catheter ablation. Patients who did not come regular follow-up after ablation were excluded. Thus, 131 patients were included. The patients were divided two groups according to spontaneous typical Afl development before or after AF ablation. They were compared in terms of baseline characteristics and procedural features. Results: The mean age of the patients was 58 (48–62), 65 of them (49.6%) were male, typical Afl was observed in 20 patients (15.2%). The frequency of male gender was higher (80.0% vs 44.1%, p=0.003), the left ventricular (LV) ejection fraction was lower (56.2±10.9% vs 60.7±6.7%, p=0.015), LV end-diastolic diameter was higher [50.0 (48.2–53.0) vs 47.0 (44.0–49.0), p<0.001), the left atrium diameter was higher (41.4±4.5 vs 38.4±4.5, p=0.008), and the right atrium (RA) diameter was higher (41.6±3.5 vs 36.8±3.7, p<0.001) in patients with typical Afl than in those without it (Figure 1a). Laboratory measurements, drug use, and procedural characteristics were similar between groups. A logistic regression analysis demonstrated that male gender [OR: 4.5, 95% CI: 1.01–20.03, p=0.048) and the RA diameter [OR: 1.57, 95% CI: 1.22–2.02, p<0.001] were independent predictors of the presence of typical Afl (Figure 1b). A Receiver Operating Characteristic curve showed that optimal cut-off value of the RA diameter to predict the presence of typical atrial flutter was 40.5 mm (AUC: 0.843, sensitivity %80, specificity %85, p<0.001) (Figure 2). Conclusion: A RA diameter greater than 40.5 mm may predict the presence of spontaneous typical Afl in patients undergoing catheter ablation for AF. This information can help to identify patients who would benefit from CTI ablation in the same session as AF ablation. Funding Acknowledgement: Type of funding sources: None.